Collection of Foundation Assets That Disbanded Due to Bankruptcy in Company Law - Cahyo Hening Wahyu Rino (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Foundation is a legal entity to which the rights and obligations provided for by the Legislation are attached. Law Number 28 of 2004 concerning Foundations regulates the establishment of the Foundation's legal entity until the dissolution of the Foundation. One of the reasons for the dissolution of the Foundation was bankruptcy, and after the Foundation was declared bankrupt by the court, the Foundation's assets had to be liquidated by liquidators or curators. In this paper, a problem formulation is put forward, namely how to reserve the assets of a Foundation that was dissolved due to bankruptcy? The result of this research is that if a Foundation disbands, its assets will be liquidated and the remaining assets resulting from liquidation will be handed over to other Foundations that have similar activities to the disbanded Foundation. In the event that the remaining proceeds of liquidation are not handed over to another Foundation which has similar activities, the remaining assets may be handed over to another legal entity which has similarities in activities to the dissolved Foundation, and if this is regulated in the Law concerning that legal entity. And if the two options above are not exercised, the wealth will be handed over to the State and its use will be carried out in accordance with the activities of the disbanded Foundation.